80 years of research on planarians (Platyhelminthes, Tricladida) from Sardinia, Italy: an annotated checklist - Stocchino, Giacinta Angela (Zootaxa, 2018)
An annotated checklist is presented of the triclad fauna of the island of Sardinia, Italy, including an update of their geographic distribution and new records for several species. All three families of European freshwater planarians are represented on the island, viz. Dugesiidae (3 genera, 9 species), Planariidae (3 genera, 2 species), and Dendrocoelidae (1 genus, 3 species), inhabiting surface and subterranean waters. Besides freshwater species, over the last decades also land planarians (Geoplanidae) have been recorded.